A Case Study Using Papaya Leaf Extract to Reverse Chemotherapy-Induced Thrombocytopenia in a GBM Patient. (January 2022) - Koehler, Abigail; Rao, Rohan; Rothman, Yehudit; Gozal, Yair M.; Struve, Timothy; Alschuler, Lise; Sengupta, Soma
Chemotherapy-induced thrombocytopenia (CIT) is a critical condition in which platelet counts are abnormally reduced following the administration of chemotherapeutic compounds. CIT poses a treatment conundrum to clinicians given the increased risk of spontaneous bleeding, obstacles to surgical management of tumors, and exclusion from clinical trials. Treatment of CIT involves the removal of the offending agent combined with platelet infusion or thrombopoietin agonist treatment. However, due to the autoimmune and infection risks associated with infusions, this treatment is only reserved for patients with critically low platelet counts. One potential solution for patients in the mid to low platelet count range is Carica papaya leaf extract (CPLE). In this case, we report the novel use of CPLE as a method of bolstering platelet counts in a patient presenting with CIT. The patient was initiated on CPLE therapy consisting of 1 tablespoon twice daily with meals. Following CPLE treatment, the patient's platelet counts rebounded from less than 10, 000/µL to 113, 000/µL. This clinical vignette supports the use of CPLE in the clinical context of CIT when thrombopoietin agonists are not a viable option. The potential benefits of CPLE as a method for increasing platelet count deserve further exploration, especially as a treatment option for refractory patients or those ill-suited for other traditional thrombocytopenia therapies.